The role of volatile organic compounds emitted by nematophagous fungi in the interaction with Meloidogyne spp. - Pacheco, Paulo Victor Magalhães (2022)
The potential of nematophagous fungi as biological control agents of plant-parasitic nematodes (PPNs) has been extensively studied. However, there is little information about the role of volatile organic compounds (VOCs) produced by nematophagous fungi in the interaction with PPNs. Therefore, this work aimed to evaluate the effect of VOCs emitted by nematophagous fungi on the trophic interaction with the different stages of the life cycle (eggs and juveniles) of Meloidogyne sp. (root-knot nematodes). In the first article, the role of VOCs emitted by the nematophagous fungus Pochonia chlamydosporia (Pc-10) in the trophic interaction with M. incognita was revealed. The VOCs emitted by P. chlamydosporia reduced M. incognita eggs hatching and also attracted M. incognita second-stage juveniles (J2). The 1,4-dimethoxybenzene compound is the major component of the volatiloma of the P. chlamydosporia strain Pc-10. The 1,4-dimethoxybenzene showed fumigant and non-fumigant nematicide activity against M. incognita, in addition to attracting the M. incognita J2. In the second article, it was demonstrated that VOCs produced by nematophagous fungi (P. chlamydosporia, Purpureocillium lilacinum, Arthrobotrys conoides and Duddingtonia flagrans) reduced M. javanica eggs hatching. In addition, VOCs emitted by P. chlamydosporia, P. lilacinum and A. conoides attracted M. javanica J2. On the other hand, VOCs from D. flagrans repelled the nematode. Twenty-two VOCs were identified from the valotiloma of these fungi. The fungi were separated into three different sets by principal component analysis (PCA). One set comprising P. lilacinum and A. conoides and two other sets with D. flagrans and P. chlamydosporia, respectively. In the greenhouse test, the VOCs emitted by P. lilacinum and the compound 1,4-dimethoxybenzene controlled M. javanica and were not toxic to the eggplant plants.